2017
DOI: 10.4088/pcc.16m02005
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Injectable Antipsychotics for Schizophrenia

Abstract: The findings of the current research suggest that medication type, frequency of medication appointments, and program type may be key in increasing and maintaining LAI adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The most commonly prescribed medications were paliperidone palmitate (31%), aripiprazole LAI (25%) and haloperidol decanoate (20%). These results are in line with data from some of the previous studies [ 42 , 74 , 75 ], while, in others, prescription rates appeared to be extremely heterogeneous [ 40 , 41 , 44 ]. This is likely to be associated with a number of factors influencing local prescribing patterns and with the different recruitment periods across studies (and therefore different availability of SGA LAIs).…”
Section: Discussionsupporting
confidence: 91%
“…The most commonly prescribed medications were paliperidone palmitate (31%), aripiprazole LAI (25%) and haloperidol decanoate (20%). These results are in line with data from some of the previous studies [ 42 , 74 , 75 ], while, in others, prescription rates appeared to be extremely heterogeneous [ 40 , 41 , 44 ]. This is likely to be associated with a number of factors influencing local prescribing patterns and with the different recruitment periods across studies (and therefore different availability of SGA LAIs).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, it is difficult to interpret our data in the light of available literature, considering that most studies do not focus on people who are incarcerated (Llorca et al ., 2018) and differences in local clinical practice could impact on prescriptional attitudes (Ostuzzi et al ., 2018). Indeed, the discrepancy in patterns of prescription could be explained by differences in refundability and socio-economic context, or by the progressive introduction of depot formulation for SGAs (McCreath et al ., 2017). In the context of these considerations, some pragmatic aspects can be listed to explain the large use of FGA-LAIs in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that long-acting injectable antipsychotics are associated with better treatment compliance [47][48][49][50]. In light of this information, it can be argued that long-acting antipsychotic treatment may decrease care burden by increasing treatment compliance.…”
Section: Discussionmentioning
confidence: 99%